USING THE DISTANCE TECHNOLOGIES IN METHODICAL TRAINING OF FUTURE TEACHERS OF BIOLOGY - Grytsai Н.Б. (Journal of Information Technologies in Education (ITE), 2016)
The article is justified the urgency of introducing the elements of distance learning in methodical training of future teachers of biology. The essence of the concepts of «distance learning» and «distance learning technologies», highlights to the views of different scholars. The author is found out that the distance learning can be proceeding through various means of communication: mail, phone, email, and telecommunications. Today the most common e-distance learning is made with the help of computer information and communication technologies. The author analyzes the results of a survey of teachers of biology on their use of innovative learning technologies. It was found out that in using the distance technology by the universities of Ukraine in their methodical training of future teachers is not enough. The author justified to specified difficulties in implementing the distance learning in higher education. The national and international experience with elements of distance learning in methodical training of future teachers of biology has been described by the author. The structure of the distance course by the subject «Methods of teaching biology» has been opened. A methodical portal to the students’ teaching practice has been proposed. The recommendations for implementation the distance learning technologies in the educational process of higher educational institutions of Ukraine to prepare a new generation of biology teachers that is competitive and competent has been made.